A New Approach to Social Assistance: Latin America’s Experience with Conditional Cash Transfer Programs - Rawlings, Laura B. (World Bank, Washington, DC, 2012)
Conditional cash transfers (CCTs) are an innovative and increasingly popular approach to social assistance. They provide money to poor families contingent upon certain behavior, usually investments in human capital such as keeping children in school or taking them to health centers on a regular basis. These programs are perhaps the clearest policy manifestation of a new line of thinking on the long-term role of social assistance programs. Not only are they instruments for short-term poverty alleviation, but they also encompass longer-term economic growth and human capital development objectives. They have been adopted internationally and in several countries they have been scaled up to become integral components of poverty alleviation strategies.